Determinants of Learning Motivation Barriers in Islamic Religious Education: A Qualitative Analysis in a Pesantren-Based Junior High School - Nikmah, Azimatun; Sulistyani, Dwi Indah; Mukarromah, Nabila Wasilatul; Yanti, Yulia Citra Ayunda Destri; Anshori, Muhammad (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study aims to examine the barriers and determinants of students’ learning motivation in Islamic Religious Education (PAI) within a pesantren-based junior high school context. It specifically investigates how pedagogical practices, teacher competencies, students’ physical readiness, and institutional environments interact to influence students’ engagement and participation in PAI learning. This research employed a qualitative case study design conducted at SMP Islam Nurul Ulum. Data were collected through classroom observations, in-depth semi-structured interviews with teachers and students, and document analysis. Data analysis followed an interactive qualitative model consisting of data condensation, data display, and conclusion drawing. Triangulation of sources and techniques, prolonged engagement, and member checking were applied to ensure the credibility and trustworthiness of the findings. The results indicate that students’ learning motivation remains suboptimal, as reflected in low classroom participation, passive behavior, limited discussion involvement, and feelings of boredom and fatigue. The study identifies interconnected internal and external barriers. Internal factors include students’ physical and psychological exhaustion due to intensive pesantren routines, which reduce concentration and readiness to learn. External factors include lecture-dominated and teacher-centered instruction, limited implementation of innovative models such as Problem Based Learning, insufficient teacher digital literacy, and inadequate learning facilities, particularly technology-based media. These barriers operate simultaneously and systematically weaken students’ intrinsic motivation. This study provides a contextual and ecological perspective by situating learning motivation within the unique ecosystem of a pesantren-based school, an area rarely explored in existing motivation research. It conceptualizes motivation not merely as an individual attribute but as a systemic outcome shaped by pedagogical, environmental, and institutional conditions. The findings contribute theoretically by integrating contemporary motivation theories with Islamic boarding school education and practically by offering evidence-based recommendations for curriculum contextualization, participatory teaching strategies, teacher professional development, and institutional policy improvement to enhance student engagement in PAI learning.